Reactivation of coccidioidomycosis in a fit American visitor. Issue 9 (1st September 1998) - Williams, F M K; Markides, V; Edgeworth, J; Williams, A J
Abstract : The case history is presented of an American visitor, known to have had primary coccidioidomycosis previously, who became very unwell during a visit to the UK. Despite consideration of reactivation of coccidioidomycosis from the outset, other pathogens were identified while Coccidioides immitis was not initially, leading to a delay in treatment.